Hydrogen-enhanced grain boundary vacancy stockpiling causes transgranular to intergranular fracture transition. (15th October 2022) - Ding, Yu; Yu, Haiyang; Lin, Meichao; Zhao, Kai; Xiao, Senbo; Vinogradov, Alexey; Qiao, Lijie; Ortiz, Michael; He, Jianying; Zhang, Zhiliang
Abstract: The attention to hydrogen embrittlement (HE) has been intensified recently in the light of hydrogen as a carbon-free energy carrier. Despite worldwide research, the multifaceted HE mechanism remains a matter of debate. Here we report an atomistic study of the coupled effect of hydrogen and deformation temperature on the pathway to intergranular fracture of nickel. Uniaxial straining is applied to nickel Σ5(210)[001] and Σ9(1-10)[22-1] grain boundaries with or without pre-charged hydrogen at various temperatures. Without hydrogen, vacancy generation at grain boundary is limited and transgranular fracture mode dominates. When charged, hydrogen as a booster can enhance strain-induced vacancy generation by up to ten times. This leads to the superabundant vacancy stockpiling at the grain boundary, which agglomerates and nucleates intergranular nanovoids eventually causing intergranular fracture. While hydrogen tends to persistently enhance vacancy concentration, temperature plays an intriguing dual role as either an enhancer or an inhibitor for vacancy stockpiling. These results show good agreement with recent positron annihilation spectroscopy experiments. An S -shaped quantitative correlation between the proportion of intergranular fracture and vacancy concentration was for the first time derived, highlighting the existence of a critical vacancy concentration, beyond which fracture mode will be completely intergranular. Graphical abstract: Image, graphical abstract